2017
DOI: 10.15244/pjoes/68879
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effects of High Levels of Nutrients on Seed Germination and Root Elongation

Abstract: IntroductionSpring and thermal ponds are important elements of a landscape, and thermal water is among the best environmental geoindicators [1][2]. Earlier studies have demonstrated that the chemistry of thermal ponds is largely influenced by the specific geological setting [2]. The use of thermal water for geochemical energy and improving health is also important [3]. Many earlier studies have demonstrated that thermal water has effects on the human body, e.g., on skin regeneration and the Pol. J. Environ. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…In the study, not all sediment samples gave a toxic response of tested organisms. The organic matter, total nitrogen, and other nutrients are essential for growth of producers in the aquatic ecosystem (Kundrat et al 2017; Jung 2017). In our studies, it was demonstrated that the some sample of sediments had stimulant effects of plants growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, not all sediment samples gave a toxic response of tested organisms. The organic matter, total nitrogen, and other nutrients are essential for growth of producers in the aquatic ecosystem (Kundrat et al 2017; Jung 2017). In our studies, it was demonstrated that the some sample of sediments had stimulant effects of plants growth.…”
Section: Resultsmentioning
confidence: 99%
“…In our studies, it was demonstrated that the some sample of sediments had stimulant effects of plants growth. Kundrat et al (2017) found that the high mineral level of the bottom sediments had stimulant effect on seed germination and roots growth of S. alba. Czerniawska-Kusza et al (2006) also demonstrated that higher amount of organic matter and nutrients in bottom sediments stimulated root growth of S. alba and L. sativum.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the importance of soil ions in seed germination, because plant seeds are highly sensitive to the soil environment, seed germination has been widely used to monitor toxicity in contaminated ecosystems [52]. A detailed study reported how high levels of nutrients in water and sediments from three different sources (river, thermal ponds, and control ponds) recollected in Albanis affected the germination of Sinapis alba L. seeds with toxic and/or stimulant effects [53]. No significant differences on seed germination were found among the three nutrient sources.…”
Section: Importance Of Soil Nutrients In Seed Germination Developmenmentioning
confidence: 99%
“…De acordo com Carniato et al (2007), Costa (2010) e Lapa et al (2014), os testes crônicos são caracterizados por permanecerem um longo período, em parte ou abrangendo todo o ciclo de vida do organismo-teste, exposto ao potencial contaminante tóxico. Os testes agudos são realizados em laboratórios, onde as condições são específicas e controladas, reduzindo a (FANTIN et al, 2009;YERUSHALMI et al, 2010;HIMANEN et al, 2012;BEDELL et al, 2014a;BEDELL et al, 2014b;EMAMI et al, 2014;MACÍA et al, 2014;KUNDRÁT et al, 2017;SONG et al, 2017;ZHANG et al, 2017;KOHATSU et al, 2018). Para a realização dos ensaios fitotóxicos, adota-se o controle que é uma solução que causa efeitos previsíveis sobre os organismos indicadores.…”
Section: Introductionunclassified